Nanoparticles as flow improver of petroleum crudes: Study on temperature-dependent steady-state and dynamic rheological behavior of crude oils. (1st September 2020) - Anto, Rincy; Deshmukh, Sameerjit; Sanyal, Saheli; Bhui, Uttam K.
Highlights: Detailed characterization of the crude oil samples is done. The crude oils have different PAH structures and polar compounds present in it. Effect of silica and alumina nanoparticles on the rheology of crude oil is analyzed. The nanoparticles (silica and alumina) exhibit potential in decreasing the viscosity of crude oil. The nanoparticles improve the flow behavior by altering the viscoelastic network. Abstract: With the present energy scenario, the oil companies are persuading to exploit crude oil resources with high viscosity and an extreme chemical composition which makes production and transportation complex. The rheology of crude oil is related to the chemical components present in them where the molecular structure of polar polycyclic aromatic hydrocarbon (PAH) plays an important role. The emergence of nanotechnology in this aspect may provide a better solution for production optimization from the subsurface reservoir as well as flow assurance in surface transportation. The present study investigates the rheological behavior of two crude oils that are chemically different at the molecular level which is demonstrated by spectroscopic methods viz. UV–visible, Fluorescence and FTIR spectroscopy. Steady-state and dynamic rheological experiments carried out with nanoparticle-free and nanoparticles added crude oil clearly exhibits that at different temperature ranges, the nanoparticles help in improving the flow properties by modifying the viscoelastic-network. The silica nanoparticles produced a higher reduction in viscosity compared to alumina nanoparticles and showed different effects on the behavior of both the samples. Thus, nanoparticles could be an important agent for flow assurance, where the proper molecular-level characterization of crude oils would help in selecting the nanoparticles for better performance.